Verba Membawa “Ngaba” dalam Bahasa Bali Kajian Metabahasa Semantik - Ni Kadek Dwi Artini (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2022)
Language is a means of communication between humans in everyday life, therefore humans are actors who determine the meaning of the communication. Balinese as the mother tongue used by Balinese people who still pay attention to the order in speaking. This can be seen from the many uses of words in Balinese which in this millennial era are starting to be abandoned. In fact, it is not uncommon for urban and rural people to not understand the language, one of which is verbs. There are many types of verbs in Balinese, but the researcher is interested in one verb, namely the verb carrying "Ngaba" in Balinese which is studied using Natural Semantic Metalanguage (MSA) theory. The verb carrying "ngaba" has 15 equivalent forms, namely as follows " Nyuwun, Natad, Ningting, Ngandong, Ngandeng, Nikul, Nyangkil, Nyunggi, Nyingal, Ngajang, Nampa, Mondong, Nengteng, Ngemel, Natuh ". Each has its own differences which can be seen from the procedure for carrying goods with the tools used, the subject and the object carried. The verb carrying “ngaba” in Balinese has two different meanings, namely doing and happening, which can be explained by the explication technique “X does something to Y”, something that good/bad happens to Y”. This difference in meaning is obtained from the analysis of the original meaning with uncompositional polysemy.